Fenomena ‘Entertainment Architecture’ di Indonesia dan Perkembangan dalam Arsitektur - Nur Endah Nuffida; Josef Prijotomo; Murni Rachmawati (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
The entertainment architecture phenomenon that started in many developed countries in the second half of the 20th century has marked the birth of architectural designs whose primary purpose is to provide interactive entertainment for their users. This literature study aims to analyze a similar phenomenon that grows as an archetype of architectural designs, particularly in Indonesia. The method used in this study is a qualitative research method with a naturalistic paradigm. This study aims to investigate and find the meaning of